Urushiol-based benzoxazine copper polymer with low surface energy, strong substrate adhesion and antibacterial for marine antifouling application. (10th October 2021) - Chen, Jipeng; Jian, Rongkun; Yang, Ke; Bai, Weibin; Huang, Chunmei; Lin, Yucai; Zheng, Binbin; Wei, Fangfang; Lin, Qi; Xu, Yanlian
Abstract: Biofouling is a common problem, has serious impact on the biomedical applications and maritime activities by human beings, and developing eco-friendly antifouling coatings is the key to the prevention of biofouling. Traditional low surface energy antifouling coatings, such as silicones and fluororesins, have the inherent defects of weak substrate adhesion and poor static antifouling performance. Herein, a low surface energy marine antifouling coating, urushiol-based benzoxazine copper polymer (UBCP), was synthesized using natural product urushiol and n -octylamine, paraformaldehyde as the reactants, and then CuCl2 as the catalyst for further reaction. UBCP can be cured into films at room temperature, which have strong substrate adhesion, smooth and dense surface, and controllable release of effective copper ion at minimized concentrations. Moreover, UBCP exhibits excellent antifouling performance, with both fouling release and antifoulant release characteristics. The antibacterial performance of UBCP towards typical Gram-negative bacteria ( E. coli ) and Gram-positive bacteria ( S. aureus ) both reach almost 100%, while its ability to inhibit algal activity is above 99%, and the surface of UBCP can effectively prevent microbial adhesion. In summary, UBCP is a highly effective and eco-friendly coating material and provides a promising approach to address the economic and operational issues caused by marine biofouling. Graphical abstract: Image 1 Highlights: UBCP was synthesized using natural product urushiol, and catalyzed by copper chloride. UBCP is a low surface energy coating with strong substrate adhesion. UBCP exhibits excellent antibacterial and antifouling performances. The antifouling mechanism is synergistic effect of antifoulant release and fouling release.